Post-operative delirium: a review of diagnosis and treatment strategies - Cunningham, Jessica; Kim, Luke Dogyun (Journal of Xiangya Medicine; Vol 3 (February 2018): Journal of Xiangya Medicine, 2018)
Delirium, a syndrome characterized by disturbances in consciousness and attention, is a serious post-operative complication. Medical professionals have been trying to manage delirium for the past 2,000 years, and yet the pathophysiology and the best treatment remain unclear. Failure to diagnose and adequately treat delirium creates harmful situations for patients. Delirium has been shown to be associated with longer lengths of stay, facility discharges, and increased mortality. The following review highlights what is currently known about post-operative delirium (POD) and ways to best manage it. This review will explore risk factors in both cardiac and noncardiac surgery, discuss risk stratification models, examine commonly used tools to diagnose delirium, and evaluate current evidence as it relates to possible ways to treat delirium. For patients experiencing POD, geriatric consultation and multi-component interventions have both been shown to reduce the incidence of delirium. Current literature does not support the use of antipsychotics, benzodiazepines, cholinesterase inhibitors, or melatonin in the management of POD. Finally, intraoperative dexmedetomidine has not been associated with lower rates of delirium, but its use postoperatively in the ICU has been linked to less delirium when compared to propofol. At this time, non-pharmacological measures remain the hallmark of treatment. Continued research in the best strategies for delirium management is needed.